Metaphor as Invective in the Genre of Internet Commentary: A Focus on German Political Discourse - D. D. Kuchina (Дискурс профессиональной коммуникации, 2023)
This article presents the results of a linguo-stylistic analysis of a Germanlanguage commentary within the context of public political internet discourse. The analysis aims to identify distinctive features specific to this genre. Empirical material consists of over 200 comments on internet posts made by the German political party “Alternative for Germany,” selected through random sampling. The study applies both general scientific and linguistic methods, such as discourse analysis and contextual analysis. The relevance of this chosen topic is justified by the need for research in the field of internet linguistics, particularly in addressing genre-related issues. The goal is to determine, identify, and describe the characteristic features of commentary as an internet text. The article thoroughly examines the approaches taken by German linguists to define the concept of “invective,” encompassing lexical-semantic perspectives, speech act theory, and post-structural discourse analysis. Additionally, the analysis of the material reveals that invective is a hallmark of German political internet discourse, with manifestations in both explicit and implicit forms. The article discusses implicatures, arising through irony and metaphorization. The author concludes that metaphor can serve as a tool of persuasion. Metaphor, as a persuasive device, involves the intentional alteration of the mental representation of a given object based on the metaphorical image imposed by the manipulator. This typically includes exaggeration in some aspects of the metaphorically represented phenomenon while diminishing others.